MODERN APPROACH TO TEACHING PHYSICAL AND COLLOIDAL CHEMISTRY AT UNIVERSITY - Ruziev I. Kh.; Mukhamadiev A. N.; Kuldosheva L. S. (International Journal of Innovations in Engineering Research and Technology, 2024)
This article explores modern methods of teaching physical and colloidal chemistry in higher education. Innovative approaches aimed at increasing the effectiveness of learning and active interaction of students with educational material are highlighted. Methods are considered that promote the development of critical thinking, the practical application of theoretical knowledge and the formation of skills in physical and colloidal chemistry. Attention is paid to the use of modern educational technologies, interactive forms of learning and student collaboration in the educational process.